Wearable technology for cardiovascular performance: A systematic review of smartwatch applications in fitness training - Yunus, Moch; Wahyudi, Nanang Tri; Aditya, Ronal Surya; Puriastuti, Alifia Candra; Alrazeeni, Daifallah M.; Sari, Gadis Meinar; Septiananda, Farsya Hidayah; Manggolono, Lintang Nirmalasari Gemalochaya (Universitas Negeri Malang, 2025)
Background: Wearable technologies such as smartwatches have revolutionized cardiovascular fitness training through real-time monitoring and personalized exercise interventions. However, the effectiveness of smartwatch apps in improving cardiovascular performance still needs to be systematically evaluated. Objective: This study aims to assess the contribution of smartwatch apps in improving cardiovascular fitness training using a systematic review based on the PRISMA framework. Methods: The research questions were designed using the PICO (Population, Intervention, Comparison, Outcome) model. A literature search was conducted in PubMed, Scopus, Google Scholar, Web of Science, and Crossref, focusing on articles published in 2020-2025 that met the inclusion criteria. Result: The results showed that smartwatches improved exercise efficiency through real-time feedback, user motivation, and AI-based recommendations. It also improved exercise adherence and cardiovascular health outcomes. However, sensor accuracy, algorithm reliability, and variations in user engagement remain challenging. Conclusion: Smartwatch apps have great potential in optimizing cardiovascular fitness training. Future research needs to focus on improving sensor accuracy, refining AI interventions, and long-term user engagement to maximize their impact.